2019
DOI: 10.12659/msm.915108
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin2 Exaggerates Cardiomyocyte Hypoxia Injury by Inhibiting Integrin β3 Signaling

Abstract: Background The neutrophil inflammatory protein, lipocalin-2 (NGAL), is elevated in certain forms of cardiac hypertrophy and acute heart failure. However, the specific role of NGAL in cardiac hypoxia injury is unclear. This study aimed to elucidate the functional role of NGAL in cardiomyocyte hypoxia injury. Material/Methods Neonatal rat cardiomyocytes were transfected with adenovirus [(Ad-NGAL] to overexpress human-NGAL and then were exposed to hypoxia for 24 h to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Neutrophils rely on Lcn2 to generate ROS while fighting bacteria 22 . However, this defense mechanism can become deleterious, damaging ischemic cardiomyocytes 23 , 24 . Serum LCN2, also known as neutrophil gelatinase-associated lipocalin (NGAL), increases in patients with MI and heart failure and predicts infarct mortality and adverse outcomes 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Neutrophils rely on Lcn2 to generate ROS while fighting bacteria 22 . However, this defense mechanism can become deleterious, damaging ischemic cardiomyocytes 23 , 24 . Serum LCN2, also known as neutrophil gelatinase-associated lipocalin (NGAL), increases in patients with MI and heart failure and predicts infarct mortality and adverse outcomes 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia exacerbates cardiomyocyte injury through Wnt3a-Sirt3 and cardiomyocyte apoptosis [28]. Inhibition of integrin ß3 signaling can deteriorate hypoxia injury of cardiomyocytes through inflammatory response, and apoptosis [29]. Resveratrol protected against hypoxia-induced neonatal rat cardiomyocytes injury through regulating Sirt1/p53-mediated apoptosis and NLRP3-mediated inflammation [30].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that NE deletion increased P-Akt levels in the heart post-MI ( Figure 4 ). Akt has been reported to reduce inflammatory responses in various cells, including cardiomyocytes [ 21 , 22 , 23 ]. Thus, a decrease in Akt signaling induced by NE may also contribute to excessive inflammation post-MI.…”
Section: Discussionmentioning
confidence: 99%